(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The text presents issue no. 24 of Móin-Móin Magazine - Studies in The Arts of Puppetry, with the theme Training experiences in cyberspace and creative processes in social isolation. To do so, it raises the questions launched as a provocation to the authors of this call and gives a brief account of the migration of the activities of the Extension Program Professional Training in Santa Catarina’s Theater, in which the edition of the journal is inserted, for the virtual mode.